2012
DOI: 10.1007/s11096-012-9722-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventive counselling for public health in pharmacies in South Germany

Abstract: Pharmacists are active in many different prevention subjects and there is a great interest in pharmacy-based preventive care counselling in the Bavarian population. Very few structured, well planned and evaluated preventive projects have been conducted in Bavarian community pharmacies. Further surveys are needed to analyse the benefit of pharmacy-based preventive care counselling for the Bavarian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
5
1
1
Order By: Relevance
“…This was in contrast to a study that showed that up to 51% of community pharmacies in a province in Germany conduct a health campaign at least once per year [49]. Factors identified as barriers to community pharmacists' involvement in delivery of health promotion and education campaigns included lack of time, poor training, lack of physical space, and inadequate knowledge and skill specific to the target subject [45], [46], [47], [48].…”
Section: Health Promotion Services and Educational Campaignscontrasting
confidence: 69%
“…This was in contrast to a study that showed that up to 51% of community pharmacies in a province in Germany conduct a health campaign at least once per year [49]. Factors identified as barriers to community pharmacists' involvement in delivery of health promotion and education campaigns included lack of time, poor training, lack of physical space, and inadequate knowledge and skill specific to the target subject [45], [46], [47], [48].…”
Section: Health Promotion Services and Educational Campaignscontrasting
confidence: 69%
“…There are only a few previous studies that focused on pharmacists' knowledge and counselling regarding sun protection, although two-thirds of pharmacists in Bavaria (Germany) stated that pharmacies are a particularly suitable place for information on skin cancer prevention [35]. A recent study showed that pharmacists' advice can definitely play a role in customers' choices regarding sunscreen products [36], however, studies in Arizona (USA) and Iran showed knowledge deficits among pharmacists [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the response rate in our study is comparable to 15,47,48 or even higher than rates observed in other online or mailing surveys among health care providers. [49][50][51][52][53][54] Other forms of communication (e.g., texting, phone interviews) with community pharmacists should be examined in future studies. Second, the Cook and Seiford method for calculation of median consensus ranking does not specifically address the intensity of the difference between ranked items.…”
Section: Discussionmentioning
confidence: 99%